Behavior of Working Mothers in Exclusive Breast Milk in The Work Area of Bulili Public Health Center - Rasyika Nurul Fadjriah; Faralizayani; Sadli Syam (Media Publikasi Cendekia Indonesia, 2022)
This study aimed to determine working mothers' behavior in exclusive breastfeeding in the Bulili Health Center Work Area, South Palu District. The research method applied qualitative with a case study approach. The research informants were 13, determined by the purposive sampling technique. The results showed that the predisposing factors with knowledge and attitude variables were still limited; the informants did not know the exact meaning of exclusive breastfeeding, the importance of exclusive breastfeeding, and the benefits of exclusive breastfeeding. Supporting factors with health facilities infrastructure and facilities at work variable are not yet available optimally. While the family support variable can be said to be lacking, this is influenced by the lack of family knowledge regarding exclusive breastfeeding. The definition of exclusive breastfeeding is still relatively low also about attitudes, even due to the lack of knowledge, facilities, and infrastructure that support exclusive breastfeeding, such as lactation rooms; in this study, the support provided by the family is still relatively low